2009 IEEE International Reliability Physics Symposium 2009
DOI: 10.1109/irps.2009.5173325
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown voltage walkout effect in ESD protection devices

Abstract: Using experimental and numerical simulation analysis the breakdown voltage walkout effect has been studied in 40 V ESD protection devices based on extended drain MOS devices implemented in a 5 V CMOS process. A similar effect has been observed in 100 V and 24 V BiCMOS processes. The physical mechanism of this effect is revealed as the result of hot electron capture in the thick field oxide of the extended drain region. To address this, a method to reduce the walkout effect in high voltage ESD devices is propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Since LDMOS devices are operated under high voltages, the drain breakdown voltage (BVdss) is a key device parameter. It has been reported that BVdss walkout (BVdss increase) is observed after either repeated BVdss measurements [1–3] or hot‐carrier stress [4], leading to BVdss instability. Previous literatures [1–4] mentioned that the physical mechanism leading to BVdss walkout is the reduced local electric field near the breakdown point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since LDMOS devices are operated under high voltages, the drain breakdown voltage (BVdss) is a key device parameter. It has been reported that BVdss walkout (BVdss increase) is observed after either repeated BVdss measurements [1–3] or hot‐carrier stress [4], leading to BVdss instability. Previous literatures [1–4] mentioned that the physical mechanism leading to BVdss walkout is the reduced local electric field near the breakdown point.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that BVdss walkout (BVdss increase) is observed after either repeated BVdss measurements [1][2][3] or hot-carrier stress [4], leading to BVdss instability. Previous literatures [1][2][3][4] mentioned that the physical mechanism leading to BVdss walkout is the reduced local electric field near the breakdown point. Such a field reduction is caused by avalanche breakdown or hot-carrier-induced injected oxide charge or interface states (N IT ).…”
mentioning
confidence: 99%